Aplikasi Private Cloud Storage untuk Menyimpan Data Operasional Program Studi Teknik Informatika dan Sistem Informasi Bisnis Menggunakan Open Source - Michael Adi; Henry Novianus Palit; Andreas Handojo (Jurnal Infra, 2017)
The Department of Infomatics Engineering and Business Infomation System of Petra Christian University has been using shared folder to save much of its operational data, like student scoresheet, list of active students, and photos of the department for exampl. But the shared folder is very vulnerable to be accessed by someone outside of the department if they had access to the computer  that have access to the shared folder easily. This shared folder also proven to be difficult to be accessed via smartphone, because there were no dedicated application that gives user access to use operational data easily.  This Private Cloud storage is using PHP and Javascript as its programming language for the web application and Java fo the mobile application. The server that used is dedicated solely fo this application and can be accessed via public IP.The result of the application development is giving user access of their files from their smartphones. This application also verifies the user so not anybody can have access to the files that’s stod in the storage.Users can also share ther files not only to another users, but also to some groups. Users can also edit thei documents right from the website